2022
DOI: 10.21924/cst.7.1.2022.669
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption studies of KOH-modified hydrochar derived from sugarcane bagasse for dye removal: Kinetic, isotherm, and thermodynamic study

Abstract: Toxicity of methylene blue (MB) in water bodies has a negative effect on environment and living organisms. The presence of MB in water could last longer in view of the non-biodegradable characteristic. In this study, hydrochar was used as adsorbent to remove MB from aqueous solution. Hydrochar derived from bagasse was successfully prepared by hydrothermal carbonization treatment at temperature of 270oC, and pressure of 10 Bar for 30 minutes. For enhancing the adsorption ability, hydrochar was activated by addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This chemisorption process aligned with previous studies on agricultural waste [ [70][71][72]. The proximity of the coefficient of regression (R²) to unity (1) [73][74][75] was employed to assess how well the determined model suited the data, so as a result, the predicted R 2 values from the PSO model matched well with the experimental values. This is also in line with the research findings that the data follows Langmuir isotherm adsorption (monolayer).…”
Section: Adsorption Kineticssupporting
confidence: 57%
“…This chemisorption process aligned with previous studies on agricultural waste [ [70][71][72]. The proximity of the coefficient of regression (R²) to unity (1) [73][74][75] was employed to assess how well the determined model suited the data, so as a result, the predicted R 2 values from the PSO model matched well with the experimental values. This is also in line with the research findings that the data follows Langmuir isotherm adsorption (monolayer).…”
Section: Adsorption Kineticssupporting
confidence: 57%
“…As C increases, the boundary layer thickness also increases, highlighting the significance of the diffusion rate that cannot be disregarded. When the sorption process is governed by diffusion, the sorbate will be transported gradually across the layers and into the active sites of the sorbent [56]. Meanwhile, this study demonstrated that the sorption did not match the Weber-Morris model well, and the diffusion rate might be disregarded because of the presumption of the tiny particle size and thinner boundary layer.…”
Section: Resultsmentioning
confidence: 93%
“…Hydrothermal carbonization R% = 60-80 [36] Hydrochar-MgAl double hydroxide Hydrothermal route q L = 157 mg/g [56] Activated hydrochar Hydrothermal carbonization q L = 357 mg/g [50] Hydrochar Hydrothermal carbonization q L = 5.12 mg/g [58] Magnetic biochar Microwave pyrolysis q L = 144.9 mg/g [59] Activated Hydrochar Hydrothermal carbonization q L = 200.01 mg/g [60] q L is maximum Langmuir removal capacities, R% is the removal efficiency.…”
Section: Hydrocharmentioning
confidence: 99%